2020
DOI: 10.3389/fonc.2020.608911
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Cell Stress and GRP78 in Glioma to Enhance Tumor Treatment

Abstract: Glioblastoma (GBM) is the most common primary brain tumor, carrying a very poor prognosis, with median overall survival at about 12 to 15 months despite surgical resection, chemotherapy with temozolomide (TMZ), and radiation therapy. GBM recurs in the vast majority of patients, with recurrent tumors commonly displaying increase in resistance to standard of care chemotherapy, TMZ, as well as radiotherapy. One of the most commonly cited mechanisms of chemotherapeutic and radio-resistance occurs via the glucose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 131 publications
0
23
0
Order By: Relevance
“…When the ER stress response is too strong and too long, the apoptotic pathway can be initiated, which leads to abnormal cell function and finally leads to cell death. When the ER stress response capacity is low, the effective cell protection mechanism is reduced, and the sensitivity of cells to injurious stimuli is increased, which leads to or accelerates cell death (Liu et al, 2020). In our study, it was found that tunicamycin could induce ER stress in trabecular meshwork cells and increased the cell apoptosis rate.…”
Section: Discussionmentioning
confidence: 54%
“…When the ER stress response is too strong and too long, the apoptotic pathway can be initiated, which leads to abnormal cell function and finally leads to cell death. When the ER stress response capacity is low, the effective cell protection mechanism is reduced, and the sensitivity of cells to injurious stimuli is increased, which leads to or accelerates cell death (Liu et al, 2020). In our study, it was found that tunicamycin could induce ER stress in trabecular meshwork cells and increased the cell apoptosis rate.…”
Section: Discussionmentioning
confidence: 54%
“…Both surgical stress and radiotherapy and chemotherapy stress can cause the patient's stress response, causing physiological and psychological abnormalities in the patient, resulting in neurological disorders; the adrenal medulla secretes catecholamines and abnormal sympathetic activity, which in turn leads to endocrine and immune system disorders [ 20 , 21 ]. The body's stress response is physiologically mainly through the activation of the hypothalamus-pituitary-adrenal cortex endocrine axis and the sympathetic-adrenal medulla endocrine axis.…”
Section: Discussionmentioning
confidence: 99%
“…e results show that high-quality nursing intervention can significantly improve the satisfaction of patients with glioma during concurrent radiotherapy and chemotherapy and improve the compliance of patients with treatment, which is conducive to the establishment of a good doctorpatient relationship and promotes the postoperative recovery of patients. Both surgical stress and radiotherapy and chemotherapy stress can cause the patient's stress response, causing physiological and psychological abnormalities in the patient, resulting in neurological disorders; the adrenal medulla secretes catecholamines and abnormal sympathetic activity, which in turn leads to endocrine and immune system disorders [20,21]. e body's stress response is physiologically mainly through the activation of the hypothalamus-pituitaryadrenal cortex endocrine axis and the sympathetic-adrenal medulla endocrine axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is notable that there is a modest increase in mass (19 mg vs. 11.1 mg, p = 0.02) and volume (17.4 cc vs. 9.0 cc, p = 0.01) among sgRNA‐transduced cells versus control. A component of this increased tumor size among transduced cells may be related to the common practice of implantation of tumor soon after puromycin selection, as puromycin has been noted to induce cell stress changes associated with increased GB growth (Liu et al., 2020; Oguma et al., 2009). Ultimately, however, we must stress that CRISPRi screen relies on hundreds of transduced nontargeting sgRNA controls to function as the experimental controls for the candidate lncRNA sgRNAs.…”
Section: Discussionmentioning
confidence: 99%